Comparıson of Tannın-Compound Levels from Cacao Leaf Ethanol Extract (Theobroma cacao L.) by Place of Growıng - Rekhan. T, Muh Rafli; Maryam, St.; Aminah, Aminah (Universitas Muslim Indonesia, 2024)
Cacao (Theobroma cacao L.) is one of the plantations commodities in Indonesia. The most abundant part of the cacao plant are the brown leaves. Cacao leaves contain several secondary metabolite compounds, one of which is tannin. Tannin has several properties, such as being astringent, antidiarrheal, antibacterial, and antioxidant. This research aims to determine the comparison of tannin compound levels from the ethanol extract of cacao leaves (Theobroma cacao L.) using the UV-Vis spectrophotometric method. Samples were taken from three areas, namely Jeneponto, Wajo, and Malino. This research method begins with sample preparation by maceration with a 96% ethanol solvent, then a qualitative analysis test is carried out using the Thin Layer Chromatography (TLC) method, and a quantitative analysis test is carried out by standard measurement of tannic acid and determination of tannin content using a UV-Vis spectrophotometer at a maximum wavelength of 756 nm. The results showed that the ethanol extract of cacao leaves (Theobroma cacao L.) was positive for containing tannin compounds and had total tannin levels in the Jeneponto area (86.244 mgEAT/g extract), Wajo (79,417 mgEAT/g extract), and Malino (79.365 mgEAT/g extract). From the results above, it shows that the ethanol extract of cacao leaves from the Jeneponto area contains the highest levels of tannin compounds compared to the other two areas.